2019
DOI: 10.3389/fmicb.2019.02441
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Chromosomal Transfer: A Distributive, Conjugative Process Creating an Infinite Variety of Mosaic Genomes

Abstract: The capacity of Mycoplasmas to engage in horizontal gene transfers has recently been highlighted. Despite their small genome, some of these wall-less bacteria are able to exchange multiple, large portions of their chromosome via a conjugative mechanism that does not conform to canonical Hfr/oriT models. To understand the exact features underlying mycoplasma chromosomal transfer (MCT), extensive genomic analyses were performed at the nucleotide level, using individual mating progenies derived from our model org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…Within a single strain, these unselected recombined regions were not distributed evenly around the chromosome, but instead often showed frequent recombination within a relatively small region of the genome (Figure 1B-D and SupplementaryFigure S2). Similar inheritance patterns have been observed after conjugation and natural transformation in several bacterial species(3,4,6,10). It has previously been suggested that localized clustering of recombination events might result from uptake of a single large donor DNA fragment followed by multiple rounds of recombination.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Within a single strain, these unselected recombined regions were not distributed evenly around the chromosome, but instead often showed frequent recombination within a relatively small region of the genome (Figure 1B-D and SupplementaryFigure S2). Similar inheritance patterns have been observed after conjugation and natural transformation in several bacterial species(3,4,6,10). It has previously been suggested that localized clustering of recombination events might result from uptake of a single large donor DNA fragment followed by multiple rounds of recombination.…”
supporting
confidence: 75%
“…To date, most experimental estimates of recombination rates have been conducted by in vitro transformation of naturally competent bacteria (3)(4)(5), but under these conditions transfer is typically limited to only small regions of the genome. A greater portion of chromosomal DNA spanning hundreds of genes could be exchanged between bacteria through some unconventional conjugal mechanisms resembling Hfr-based transfer in Escherichia coli (6)(7)(8)(9)(10). For example, mycobacterial distributive conjugal transfer and mycoplasma chromosomal transfer can promote simultaneous transfer of multiple large donor chromosomal fragments to the recipient cells, creating chimeric transconjugant genomes with unique recombination landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are phages that can transpose, plasmids that integrate like ICEs, and ICEs that can replicate like plasmids. There are also MGEs that can mobilise a whole bacterial chromosome [21,22]. It is best to think of MGEs as a continuum rather than trying to place them in neat boxes.…”
Section: Mobilome Compositionmentioning
confidence: 99%
“…Since the 1990s, studies combining comparative genomics to classical microbiology approaches showed that several mycoplasma species, most specifically those infecting ruminants, exchanged significant parts of their genomes during evolution and still retained the ability to conjugate [9][10][11]. Horizontal gene transfer (HGT) is one of the main drivers of microbial innovation and is responsible for the exchange of large gene clusters, known as genomic islands (GIs) among bacteria.…”
Section: Common and Specific Features Of Mycoplasma Genomesmentioning
confidence: 99%